Mediterranean woody plant specialized metabolites affect germination of Linum perenne at its dry and upper thermal limits - Hashoum, Hazem; Saatkamp, Arne; Gauquelin, Thierry; Ruffault, Julien; Fernandez, Catherine; Bousquet-Mélou, Anne (Plant and soil, 2020)
Aims Soil temperature and moisture impact plants not only during growth and survival but also during seed germination and interaction of seeds with the chemical environment. The quantitative impacts of either temperature and moisture or plant specialized metabolites (PSM) on germination are widely studied. However, the combined effect of PSM and moisture or temperature on germination remains poorly understood. Methods We addressed this issue by studying the effect of PSM extracted from four Mediterranean woody plants on germination speed and final percentages of a subordinate herbaceous plant, Linum perenne . Results By using hydro- and thermal time threshold models, we show how PSM interact with temperature and moisture levels to limit germination at dry and upper thermal limits, with the magnitude of effects depending on the source plant. PSM effects on germination, also observed on natural soils, persisted after their removal from the seed environment. Conclusions We conclude that the impact of climate change on reproduction of herbaceous plants can be modulated by effects of PSM from woody plants, which might exacerbate the negative impacts of global changes on biodiversity.